2D shape blending - Wang, Xiaohan (2016)
Shape blending, or shape morphing, refers to the progressive transformation from one shape to another. 2D Morphing is widely applied in the digital industries to make seamless animation. The core task of the morphing technique is to generate smooth and natural intermediate graphs to transit between different shapes. There are typically 3 problems involved in morphing, the vertex pre- processing, correspondence, and interpolation. This project has surveyed different approaches in these 3 problems. It was found that two correspondent methods investigated in this experiment don’t have significant differences. However, edge tweaking algorithm presents more natural results than vertex interpolation. These results were generated by a software tool developed in this project. This tool proposed a prototype of the user interface for applying morphing techniques. It can also save the morphing results into a gif file so that they can be viewed via other media players. This project suggests further research in the area of feature recognition of 2D shapes in order to create more natural morphing that fits human’s appreciation needs, and more efficient algorithms in terms of computational time.